2022
DOI: 10.1002/hep.32777
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers correlated with liver stiffness assessed in a multicenter study of pediatric cholestatic liver disease

Abstract: Background and Aims: Detailed investigation of the biological pathways leading to hepatic fibrosis and identification of liver fibrosis biomarkers may facilitate early interventions for pediatric cholestasis. Approach and Results: A targeted enzyme‐linked immunosorbent assay–based panel of nine biomarkers (lysyl oxidase, tissue inhibitor matrix metalloproteinase (MMP) 1, connective tissue growth factor [CTGF], IL‐8, endoglin, periostin, Mac‐2–binding protein, MMP‐3, and MMP‐7) was examined in children with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Bessho K et al reported that CXCL8 in the liver serves as a sensitive diagnostic biomarker, and perturbing the CXCL8-CXCR2 signature in the murine model could reduce the course of cholestasis and the risk of biliary obstruction, thereby increasing the overall survival ( 37 ). Leung DH et al reported that serum CXCL8 significantly correlates with liver stiffness in BA and can predict poor clinical outcomes ( 38 ). Thus, CXCL8 may be a diagnostic and prognostic biomarker and therapeutic target for BA.…”
Section: Discussionmentioning
confidence: 99%
“…Bessho K et al reported that CXCL8 in the liver serves as a sensitive diagnostic biomarker, and perturbing the CXCL8-CXCR2 signature in the murine model could reduce the course of cholestasis and the risk of biliary obstruction, thereby increasing the overall survival ( 37 ). Leung DH et al reported that serum CXCL8 significantly correlates with liver stiffness in BA and can predict poor clinical outcomes ( 38 ). Thus, CXCL8 may be a diagnostic and prognostic biomarker and therapeutic target for BA.…”
Section: Discussionmentioning
confidence: 99%
“…Transient elastography is used with increased frequency in children with chronic liver disease and is a noninvasive modality that may enhance our evaluation; however, there are limitations based on clinical availability, age cutoffs, nor has it become standard of care at all pediatric centers. The Childhood Liver Disease Research Network recently published a multicenter study investigating biomarkers of liver fibrosis and found there was a correlation with liver stiffness via transient elastography and biomarkers of fibrosis and that they varied based on type of pediatric cholestatic liver disease 13 . This study is a promising example of the research underway to better understand, monitor, and possibly intervene in a variety of pediatric chronic liver diseases and underscores the need for noninvasive tools to guide care.…”
mentioning
confidence: 85%
“…Besides, Leung et al . 42 used shear wave velocity to measure liver stiffness, an indirect measure of fibrosis. They found that MMP-7 significantly correlates with increased liver stiffness in patients with BA ( n = 187), supporting the findings of Jiang et al .…”
Section: Mmp-7mentioning
confidence: 99%
“…It is worth noting that Lertudomphonwanit et al 16 and Jiang et al 32 used different systems to evaluate histological fibrosis. Besides, Leung et al 42 used shear wave velocity to measure liver stiffness, an indirect measure of fibrosis. They found that MMP-7 significantly correlates with increased liver stiffness in patients with BA (n = 187), supporting the findings of Jiang et al 32 and Chi et al 35 In addition, many researchers have tried to screen out high-risk children who may need liver transplantation after KPE based on their serum MMP-7 concentrations.…”
Section: Mmp-7mentioning
confidence: 99%
See 1 more Smart Citation